Desenvolvimento, avaliação e aplicação de um dispositivo de preparo de amostras automatizado para extrações assistidas por campos elétricos - Victor Hugo de Miranda Boratto (2023)
The sample preparation step brings with it numerous obstacles such as the high demand for time and cost, in addition to being associated with the step with the greatest source of error in a chemical analysis, especially when performed manually at high frequencies. Thus, this work proposes the construction and evaluation of an automated sample preparation device for extractions assisted by electric fields. In addition, the work aims at the application for the extraction of doxorubicin in synthetic urine samples and determination via digital image analysis (DIA) and UV-Vis spectrophotometry. In order to achieve the estimated objectives, the hardware was built using parts printed on a 3D printer and electronic components widely used in prototypes in the most diverse areas. Then, the control code was developed and evaluated using the C++ language for the purpose of performing the automated unit operations. The proof of concept of the device is presented in a qualitative way through the extraction of the gentian violet cationic dye. In the application of the system, different conditions for image acquisition and the factors that influence the electroextraction were evaluated, such as percentage of organic solvent in the donor phase, sample dilution and agitation of the system in a univariate way and by multivariate methods factors such as electric potential and time , being defined as optimal conditions, the electrical potential of 300V, time of 20 minutes, percentage of acetonitrile in the donor phase of 37.5%, diluting the sample in deionized water (1:1, v/v), applying agitation during the process. The method showed linearity only for DIA in the range of 0.4 – 1.4 µg mL-¹, requiring a more efficient optimization for the method involving UV-Vis spectrophotometry. The other evaluated figures of merit (precision, quantification limit and recovery) were satisfactory, considering that the objective of the work is the demonstration and functionality of the automated device.